Kesan Sistem Perancangan Sumber Perusahaan (PSP) Terhadap Sektor Awam: Kajian Kes Di Majlis Bandaraya Melaka Bersejarah (MBMB) - Farouk, Nur Farina Syaqera; Mohd Farid Fernandez, Dahlia Fernandez (Research in Management of Technology and Business, 2020)
Enterprise Resource Planning (ERP) is a set of applications that automate various processes within the organization and help organizations to handle tasks such as order processing and production scheduling, and to make financial management process more efficiently and effectively. However, the ERP system has its challenges in terms of the use and operation of the system, both to individuals and organizations. The objective of this study is to find out the impact of the ERP system used on the performance of individuals and organizations in the public sector. The method used in this study is a single case study. The respondents involved are accountants and auditors working in the finance department at the Melaka Historic City Council (MBMB). The results of the study show that ERP provides various impacts on individuals such as time savings, increased productivity, and customer relationships. ERP also saves the organizational costs, improves employee communication, and increases organizational productivity.